Synergy of Pancasila, Youth, and SDGs in Protecting the Earth - Lubis, Abdul Malik; Hamid, Rizal al (Universitas Mercu Buana, 2024)
Indonesia is one of the countries facing critical environmental sustainability issues, including deforestation, pollution, and the impacts of climate change. This article discusses how Pancasila, the role of youth, and the Sustainable Development Goals (SDGs) work together to maintain environmental sustainability in Indonesia. As the country's basic philosophy, Pancasila provides a moral and ethical foundation to support sustainable development, where the key principles are humanity, justice, and shared prosperity. Around 23.18% of Indonesia's population are youth, who have great potential to become agents of change in environmental sustainability efforts. They can do so by developing new technologies, organizing campaigns to raise public awareness, and actively participating in environmental policies. This article analyzes the role of youth and Pancasila in achieving the SDGs by using literature study methodology. It is emphasized that the role of youth in adopting environmentally friendly lifestyles and encouraging green innovations such as circular economy and renewable energy technologies is in line with the values of Pancasila and the SDG’s goals. Indonesia can achieve sustainable development while preserving the environment for future generations by working together with this synergy. In addressing the climate crisis, the synergy between Pancasila and the SDGs provides a strong moral foundation. Youth, as agents of change, play an important role in realizing a more just, inclusive, and sustainable future.